Assessing the soil moisture effects of planted vegetation on slope stability in shallow landslide-prone areas - Li, Jia; Wang, Xia; Jia, Haixia; Liu, Yang; Zhao, Yunfei; Shi, Changming; Zhang, Furong; Wang, Kaichang (Journal of soils and sediments, 2021)
Purpose Soil moisture plays an important factor to impact runoff and the slope stability, but how vegetation affects the soil moisture variability of slope stability is poorly understood. In order to compare the stability of different shrub slopes under the effect of soil moisture, four types of shrubs ( Periploca sepium , Lespedeza bicolor , Ziziphus jujuba , and Punica granatum ) are selected for ecological restoration in shallow landslide-prone areas, and the effects of rhizosphere soil moisture and plant roots on the slope stability are studied. Materials and methods Trace infiltration is applied in order to study plant roots and soil moisture impact. The shear strength of the roots slope soil under different moisture content is determined by laboratory shear strength test. The slope safety factor of different shrubs is obtained by FLAC 3D (Fast Lagrangian Analysis of Continua 3D) simulation. Results and discussion Among the four shrubs, thick roots show the greatest improvement to soil porosity, and fine and medium roots could provide more preferential flow channels for water infiltration. The soil moisture content significantly increases after planting Lespedeza bicolor . At 10% soil moisture content, the P. sepium slope safety factor is highest in four shrubs (1.39). When the soil moisture content reaches 30%, the safety factor value of the L. bicolor slope reaches the maximum, and the safety factor value of L. bicolor decreased by 25.6%. Conclusions The results show that even during the wettest condition of the soil (saturated soil moisture content 30%), the mechanical reinforcement form the L. bicolor root maintains some degree of stability. Shrubs have a good effect on enhancing the stability of slopes, especially in areas prone to shallow landslides.